Prospective study to measure the functional outcome of tibial plateau fractures - Kayath, Anand Mohan; Kayathwal, Ankit Kumar (International Journal of Research in Orthopaedics, 2019)
Background: Tibial plateau fractures are complex injuries of the knee. The tibial plateau is one of the most critical load-bearing areas in the human body. Early detection and appropriate treatment of these fractures are essential in minimizing patient’s disability in range of movement, stability and reducing the risk of documented complications. The aim of the present study is to study the outcome of tibial plateau fractures and their management. Methods: This is prospective study which comprises of 50 patients with displaced tibial plateau fracture and were treated between January 2018 to December 2018 with minimal invasive percutaneous plate osteosynthesis and cortico-cancellous screw fixation. Statistical analysis was done by Chi-square test and IBM SPSS software. Results: In our study we included 50 cases, treated with surgical procedure, 30 cases gave excellent result, 16 cases came out with good result, fair in 3 cases and 1 case had poor result. High velocity injuries have poor outcome than low velocity injuries. A single case of malunion was noted in study. Four cases had knee joint stiffness. Conclusions: We conclude that functional outcome is good in operatively treated patients. Early physiotherapy plays key role in preventing knee stiffness, use of bone grafts and good fixation important for successful outcome.